Persepsi Mahasiswa Terhadap Virtual Laboratory Pada Materi Rangkaian Listrik Sederhana - Dhimas Nur Setyawan; Astuti Wijayanti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Science learning is emphasized on the active involvement of students to find concepts. However, limited access to the use of laboratories on campus prevents students from doing practicum. Therefore, one way to do learning during the transition from the pandemic to the new normal is by practicum using a virtual laboratory. The purpose of this study was to describe students' perceptions in practical activities using a virtual laboratory on simple electrical circuit material. The method used in this research is in the form of a survey by giving questionnaires to students who take part in the virtual laboratory practicum as many as 21 students. The technique used in the analysis uses descriptive quantitative. The survey results show that students have positive perceptions of virtual laboratory activities on aspects of learning innovation, motivation, effectiveness, benefits, and presentation of practical procedures.